2019
DOI: 10.1101/778365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noncoding microdeletion in mouseHgfdisrupts neural crest migration into the stria vascularis, reduces the endocochlear potential and suggests the neuropathology for human nonsyndromic deafness DFNB39

Abstract: 1 stria vascularis, reduces the endocochlear potential and suggests the 2 neuropathology for human nonsyndromic deafness DFNB39 3 Abbreviated title: Mouse model of HGF DFNB39 deafness.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…The c.482+1986_1988del variant identified in this study has been previously reported to cause prelingual, profound deafness (DFNB39, MIM 608265) [43]. A Hgf 10 bp deletion in homozygous mutant mice, which fully encompasses the 3 bp deletion in humans, also displayed profound hearing loss at 4 weeks age (Figure 3(d)) [55]; Hgf 10 bp deletion in homozygous mice causes low expression of Hgf in the cochlea, which leads to developmental defect of the stria vascularis and reduced endocochlear potential in the cochlea [55]. The 3 bp deletion in the intronic region possibly has a similar mechanism to cause hearing loss.…”
Section: Discussionsupporting
confidence: 56%
“…The c.482+1986_1988del variant identified in this study has been previously reported to cause prelingual, profound deafness (DFNB39, MIM 608265) [43]. A Hgf 10 bp deletion in homozygous mutant mice, which fully encompasses the 3 bp deletion in humans, also displayed profound hearing loss at 4 weeks age (Figure 3(d)) [55]; Hgf 10 bp deletion in homozygous mice causes low expression of Hgf in the cochlea, which leads to developmental defect of the stria vascularis and reduced endocochlear potential in the cochlea [55]. The 3 bp deletion in the intronic region possibly has a similar mechanism to cause hearing loss.…”
Section: Discussionsupporting
confidence: 56%
“…Compensation for the loss of TBC1D24 in mouse may be provided by a paralog in the mouse genome or compensation by a gene involved in the same network or signaling pathway [ 63 ]. For example, a dominant variant of METTL13 ( DFNM1 ) completely suppresses recessive non-syndromic deafness DFNB26, associated with a variant of GAB2 with both genes functioning in the HGF/MET signaling pathway [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%